Menciptakan Kepuasan Konsumen Dengan Pengalaman Membeli Produk - Sukma Irdiana; Mohammad Noor Khairullah2 (Jurnal Ilmu Manajemen Advantage, 2019)
The number of internet users currently in Indonesia is increasingly growing, along with the development of the times and technology. One of them is the provision of food delivery services. In this research, researchers have the aim to describe how far the influence of the consumer buying experience on satisfaction and the desire to buy back online at Go Food in Surabaya. This research data was obtained through distributing questionnaires to 70 respondents using the accidental sampling method for ordering GoFood in Surabaya, who often bought using GoFood online at least three times in a period of 2 months. The data testing technique used in this research is Partial Least Square. The research proves that buying experience and online customer satisfaction sometimes does not provide a stimulus to repurchase consumers. However, optimal customer satisfaction can result in repurchases on a product or service provided. This is because buying experience and customer satisfaction does not guarantee consumers to buy back a product. However, if consumers are satisfied, consumers will spontaneously make repeat purchases. Even if consumers are satisfied, consumers will indirectly promote products to other consumers.